Postoperative Craniopharyngioma in a 10-Year-Old Girl Presenting with Central Precocious Puberty, Central Diabetes Insipidus, and Growth Hormone Deficiency - Putri Prashanti, Nyoman Ananda; Putu Wahyu Dyatmika Tanaya; I Wayan Bikin Suryawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Hypopituitarism is the most common endocrinology complication of postoperative craniopharyngioma. However, we found a 10-year-old girl with a history of postoperative craniopharyngioma presenting with central precocious puberty (CPP), central diabetes insipidus (CDI), and growth hormone deficiency (GHD). Case presentation: A 5-year-old girl experienced breast growth followed by menstruation six months later. The patient's weight was 19 kg (weight-for-age: P25-P50), height was 109 cm (height-for-age: P10-P25), and good nutritional status (Waterlow 90%). The stage of pubertal development was M2P2. There was a history of craniopharyngioma, and it was resected at the age of 2 years. After surgery, the patient developed CDI and has received desmopressin. No new tumour growth was found from evaluation with periodic MRIs every three years. After CPP was established, with increased serum levels of LH, FSH, and estradiol, GnRH agonist therapy was given at 100 mcg/kg BW every month. During five years of follow-up, the patient experienced clinical and laboratory improvement. However, the growth is only 3-4 cm/year (<P3) with short stature (height-for-age: <P3) and overweight. Low levels of IGF1 and GH were found in the stimulation test results, so the diagnosis of GHD was confirmed. The patient will receive growth hormone therapy and is expected to reach her potential genetic height (148.5 - 165.5 cm). Conclusion: Even though the craniopharyngioma tumour has been resected and no recurrence has occurred, it is crucial to evaluate the hormones produced by the pituitary thoroughly.